2021
DOI: 10.4018/978-1-7998-4993-3.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Women's Empowerment as a Tool for Sustainable Development of Higher Education and Research in the Digital Age

Abstract: The chapter deals with the global issue of advancing women's role in higher education and research (HE&R) as a mechanism for reaching the Sustainable Development Goal 5 – gender equality. Gender analysis method is employed to identify historical and current differences between women and men relative to their participation in HE&R and access to decision-making and resources therein. The focus is on the global challenge of gender disparities, including horizontal and vertical segregation, the androcentri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Correll argued that this difference might result from cultural beliefs about gender and differential perceptions of career competence among both genders. In a more recent investigation, Kurchenko et al (in press) suggested that gender inequalities resulting from unconscious male prejudice in the academic culture and structural problems affect female career prospects. In fact, Watts et al (2015) reported that female students reported significantly higher perceived career barriers than their male peers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Correll argued that this difference might result from cultural beliefs about gender and differential perceptions of career competence among both genders. In a more recent investigation, Kurchenko et al (in press) suggested that gender inequalities resulting from unconscious male prejudice in the academic culture and structural problems affect female career prospects. In fact, Watts et al (2015) reported that female students reported significantly higher perceived career barriers than their male peers.…”
Section: Literature Reviewmentioning
confidence: 99%